2011
DOI: 10.1002/pits.20589
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences and social support: Mediators or moderators between peer victimization and depressive feelings?

Abstract: Using self‐report questionnaires, a survey among 606 Dutch primary school children aged 10 to 12 years examined relationships among social support, gender, victimization, and depressive feelings. Hierarchical regression analyses confirmed that victims and bully/victims would report more depressive feelings than uninvolved children. There was no evidence that social support moderated the relationship between victimization and depressive feelings. However, social support appeared to influence the depressive feel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 54 publications
9
44
1
4
Order By: Relevance
“…Additionally, other studies have also shown that parental support may play a buffering role between victimization and internalizing distress caused by bullying (e.g., Davidson and Demaray 2007;Flaspohler et al 2009;Flouri and Buchanan 2002), and between psychological distress and NSSI (e.g., Baetens et al 2014;Tatnell et al in press). These findings are in line with the buffering hypothesis of social support (Cohen and Wills 1985;Jackson 1992) which states that social support can function as a buffer against different types of stress (Pouwelse et al 2011;Wolff et al 2014).…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Additionally, other studies have also shown that parental support may play a buffering role between victimization and internalizing distress caused by bullying (e.g., Davidson and Demaray 2007;Flaspohler et al 2009;Flouri and Buchanan 2002), and between psychological distress and NSSI (e.g., Baetens et al 2014;Tatnell et al in press). These findings are in line with the buffering hypothesis of social support (Cohen and Wills 1985;Jackson 1992) which states that social support can function as a buffer against different types of stress (Pouwelse et al 2011;Wolff et al 2014).…”
Section: Introductionsupporting
confidence: 78%
“…According to Cassidy and Taylor (2005), the influence of victimization on mental health can be explained by stress theory (Zautra 2003, in Pouwelse et al 2011. Frequent victimization and the inability to react adequately to this victimization can cause stress, fear, depression, and anger (Pouwelse et al 2011), which can subsequently trigger self-harming behaviors (such as NSSI) to cope with these emotions. Several studies have already shown that affect-regulation and self-punishment are the two most common functions of NSSI (Klonsky 2007(Klonsky , 2009.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, even a mild willingness to listen to or sympathize with the bullied victim from classmate or friends would facilitate their sense of identity and effective regulation of emotions. Unfortunately, most peers just expressed their intention to support the bullied victims in hypothetical conditions and the actual defending behavior reported by their peer reports was rare (Holt & Espelage, 2007;Pouwelse et al, 2011;Sainio et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the school environment, peer support network may provide social support in its multiple forms, such as emotional, motivational, instrumental and informational support (Flaspohler et al, 2009). A possible explanation for the mediating role of peer support was summarized by Pouwelse et al (2011), such that students who are bullied and are noticeably rejected or isolated by their peers may suffer from internalizing problems, lack of adequate social skills to resolve interpersonal conflict, and have lower self-esteem. When they get more peer support, they feel confident and, as a result, report less depression symptomology.…”
Section: Discussionmentioning
confidence: 99%